Integrative computational design and construction: Rethinking architecture digitally. Issue 4 (22nd June 2021) - Knippers, Jan; Kropp, Cordula; Menges, Achim; Sawodny, Oliver; Weiskopf, Daniel
Abstract: Increasing the construction capacity, while at the same time significantly reducing harmful emissions and consumption of nonrenewable resources, and still providing a liveable and affordable built environment, provides a great challenge for future construction. In order to achieve this, both the productivity of construction processes and the energy and resource efficiency of construction systems have to be improved in a reciprocal process. Digital technologies make it possible to address these challenges in novel ways. The vision of this Cluster of Excellence IntCDC at the University of Stuttgart and the Max Planck Institute for Intelligent Systems is to harness the full potential of digital technologies to rethink design and construction based on integration and interdisciplinarity, with the goal of laying the methodological foundations to profoundly modernize the design and construction process and related building systems by adopting a systematic, holistic and integrative computational approach. One key objective is to develop an overarching methodology of "co‐designing" methods, processes and systems based on interdisciplinary research encompassing architecture, structural engineering, building physics, engineering geodesy, manufacturing and systems engineering, computer science and robotics, and humanities and social sciences. In this way, the Cluster aims to address the ecological, economic and social challenges and to provide the prerequisites for a high‐quality and sustainable built environment and a digital building culture.